Transfer kultur w przekładzie tekstów użytkowych - Mocarz, Maria (Acta Polono-Ruthenica, 2006)
This article provides an analysis of translation methods of elements of culture in guidebooks, which belong to the so-called functional texts. There are two basic translation strategies of such lexis: 1) exotisation and 2) adaptation (most frequently combined with exotisation). The high frequency of the first strategy depends on the informative function of a given text. This function results in the lack of occurrence of adaptation, uncombined with exotisation. Moreover, the choice of the particular translation strategy is influenced by the following factors: the dynamic character of the translation norm and the impact of the tradition of interlinguistic relations.